2014
DOI: 10.1371/journal.pone.0096620
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Combined with Transarterial Chemoembolization versus Transarterial Chemoembolization Alone for Advanced-Stage Hepatocellular Carcinoma: A Propensity Score Matching Study

Abstract: AimsThe purpose of the present study was to compare the efficacies of transarterial chemoembolization (TACE) combined with sorafenib versus TACE monotherapy for treating patients with advanced hepatocellular carcinoma (HCC).MethodsWe enrolled 321 patients and selected 280 with advanced HCC (Barcelona Clinic Liver Cancer stage C) who underwent TACE therapy between February 2009 and February 2013. TACE alone (monotherapy group) was administered to 198 patients (70.7%), and the remaining 82 (29.3%) underwent repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 26 publications
3
51
2
Order By: Relevance
“…Another study compared the efficacy of TACE plus sorafenib and TACE alone in 246 advanced stage HCC patients (82 and 164 patients, respectively) after propensity score matching. Overall survival was significantly longer in the combination group than in the TACE monotherapy group (7.0 and 4.9 mo, respectively; P = 0.003) as was time to progression (2.6 and 1.9 mo, respectively; P = 0.001) [150] . These data suggest that the combination of TACE and sorafenib is most likely more efficacious than either therapy alone in advanced HCC.…”
Section: Sorafenib Combined With Tacementioning
confidence: 92%
“…Another study compared the efficacy of TACE plus sorafenib and TACE alone in 246 advanced stage HCC patients (82 and 164 patients, respectively) after propensity score matching. Overall survival was significantly longer in the combination group than in the TACE monotherapy group (7.0 and 4.9 mo, respectively; P = 0.003) as was time to progression (2.6 and 1.9 mo, respectively; P = 0.001) [150] . These data suggest that the combination of TACE and sorafenib is most likely more efficacious than either therapy alone in advanced HCC.…”
Section: Sorafenib Combined With Tacementioning
confidence: 92%
“…Several studies compared sorafenib plus TACE to sorafenib or TACE [72][73][74][75][76][77][78] [Supplementary Table 4]. A meta-analysis of sorafenib in combination with TACE that included data of 1,254 patients found that the combination improved OS and TTP in advanced HCC, but not PFS, with higher rate of severe adverse reaction in the combination group.…”
Section: Combination Of Targeted Therapy With Locoregional Therapymentioning
confidence: 99%
“…After extracting duplicates, 798 manuscripts remained, of which most were deemed irrelevant based on their title or/and abstract . Of the remaining 14 studies, four were not RCTs [14,15,25,26], two compared sorafenib with chemotherapeutic drugs [16,27], and two were subgroup analysis of prior clinical trials [12,28]. Ultimately, six studies were included in our analysis [8][9][10][11]13,29] (Figure 3).…”
Section: Study Selectionmentioning
confidence: 99%